2011
DOI: 10.1021/la105147u
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bath Deposition of ZnO Nanowires at Near-Neutral pH Conditions without Hexamethylenetetramine (HMTA): Understanding the Role of HMTA in ZnO Nanowire Growth

Abstract: Chemical bath deposition (CBD) is an inexpensive and reproducible method for depositing ZnO nanowire arrays over large areas. The aqueous Zn(NO(3))(2)-hexamethylenetetramine (HMTA) chemistry is one of the most common CBD chemistries for ZnO nanowire synthesis, but some details of the reaction mechanism are still not well-understood. Here, we report the use of in situ attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy to study HMTA adsorption from aqueous solutions onto ZnO nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 26 publications
5
117
0
Order By: Relevance
“…(1) and (2)). 13,43,44 For $pH 11 solutions, production of ZnO occurs via the equilibrium reactions shown in Eqs. (3) and (4).…”
Section: Introductionmentioning
confidence: 99%
“…(1) and (2)). 13,43,44 For $pH 11 solutions, production of ZnO occurs via the equilibrium reactions shown in Eqs. (3) and (4).…”
Section: Introductionmentioning
confidence: 99%
“…(Results on the formation of undoped ZnO-GFs as a baseline for the synthesis of CZO-GFs are also reported for completeness.) The growth of nanostructured ZnO by a solution synthesis pathway has been a topic of keen research interest for the past decade or so [10][11][12][13], motivated by the need for an inexpensive means of preparing such material with the potential for scale-up [14]. The context of our work is that of non-electrochemical routes to NW synthesis where the general method used falls into the category of chemical bath deposition (CBD).…”
Section: Introductionmentioning
confidence: 99%
“…The CBD method has typically been based on Zn(NO 3 ) 2 -HMTA chemistry (where HMTA is hexamethylenetetramine, (CH 2 ) 6 N 4 ) [11] and also involves the use of a thin-film or particulate seed layer of ZnO [12] or a metal catalyst. Recent insight on the reaction chemistry using attenuated total reflection Fourier transform infrared spectroscopy has revealed that the role of HMTA in the anisotropic deposition chemistry is one of controlling the saturation index of ZnO as described by McPeak et al [13]-these authors go on to demonstrate the growth of ZnO-NWs without HTMA, but using a pH buffer in combination with continuous KOH titration where the seeding substrate comprises a high-rugosity ZnO layer prepared by drop-coating from a ZnO nanoparticle suspension in ethanol/water. In fact, the method employed in our work is based on an even simpler technique of a repeated two-step, dropcasting and annealing sequence-where the drop-casting is akin to the seed layer preparation method of ref [13] , but doesn't involve attendant issues of that method such as pH control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, -NH 2 groups of PEI can react with Zn 2+ and Eu 3+ to form their chelates. Then, the chelates react with [29]. The growth speed of Eudoped ZnO crystals depends on the releasing speed of those ions.…”
Section: Resultsmentioning
confidence: 99%